(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The article defines the quantity of effluent of the Artsvanik tailing dam, estimates the negative impact on the river water of Norashenik and the necessity of changing the point of their discharge. Also, the discharge point of waste water was defined, which is at an altitude the Voghj River in 680 m. It is planned to transfer the wastewater directly from the mouths of the tunnels through one general pipeline and to discharge them into the Voghi River after physico-chemical and biological treatment in accordance with existing norms. The implementation of the planned measures the water of the Norashenik River will not be polluted, the water quality indicators of the Voghj River will not be deteriorated and waters of rivers will be suitable for the main sectors of water uses.